Нistorical aspect of the formation of the term «undue advantage» - Бондаренко, Ольга Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article defines the essence of the historical aspect of the origin of the concept of «undue advantage». The text analyzes the essence of the historical, etymological and substantive grounds of emergence of the term «bribe». The author focuses on problem aspects of removal of the term «bribe» from the Criminal code of Ukraine.